Tetrapod tracks from the Vera Formation (Los Menucos Group, Río Negro province, Argentina) and their bearing on the chronostratigraphy of the Los Menucos Basin - Citton, Paolo (2018)
Fil: Citton, Paolo. Universidad Nacional de Río Negro. Instituto de Investigación en Paleobiología y Geología. Río Negro, Argentina